Contribution of Property Rates to Internally Generated Fund (IGF) Mobilization in Kassena-Nankana Municipality of Ghana - Tundyiridam, Roland; Alhassan, Alhassan Yakubu; Abdulai, Abdul-Rahim (Advances in Social Sciences Research Journal, 2016)
Decentralized units need to be financially sound by having adequate resources either raised locally and/or transferred from the central government to be effective. Decentralized units in developing countries mostly depend much on external sources. However, internal revenue sources like property rates hold great potentials of reducing the dependence. This study aims at understanding how property rates contribute to revenue mobilization of District Assemblies in Ghana, using the Kassena Nankana Municipality as the focus. Case study was adopted to study extensively how property rate contributes to IGF mobilization of the area. This involved institutional interviews, document reviews and a field survey of property owners. The study revealed that rate contributed about 31.7 percent, 39.2 percent, 36.1 percent, 37.8 percent, and 30.1 percent of total IGF in 2010, 2011, 2012, 2013 and 2014 respectively. Also, the Assembly mobilizes four forms of rates: basic rates, property rates, cattle rates, and motor and car rates. Out of these rates, property rates contribute greatly to IGF of the Assembly with more than 90 percent of total rate throughout the study period. Despite higher contribution of rates to IGF, the study still found compliance to be low as about 30 percent of property owners do not pay the due rates. This was attributed to lack of trust in authorities. Innovative measures must therefore be adopted by local governments to make property owners appreciate the need to pay taxes. This will help improve property rate mobilization to help local governments move towards fiscal independence.